Country Size and Public Good Provision - Klaas Staal (Tinbergen Institute, 2004)
This paper studies the equilibrium size of countries. Individuals in smallcountries have greater influence over the nature of political decision mak-ing while individuals in large countries have the advantage of more publicgoods and lower tax rates. The model implies that (i) there exists excessiveincentives to separate, though this need not be the case for all sets of seces-sion rules studied; (ii) an exogenous increase in public spending decreasescountry size; (iii) countries with a presidential-congressional democracy arelarger than countries with a parliamentary democracy.
Keywords: D7; H1; H2; H7; 330; country size; public spending; structure of government; Landesgröße; Öffentliche Ausgaben; Öffentliche Güter; Staatsquote